(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
A field experiment was carried out at Research Station A of the College of Agricultural Engineering Sciences - University of Baghdad - Department of Field Crops in the Jadriya region for the fall season (2023) with the aim of evaluating the performance of some Egyptian varieties and comparing them with two local varieties of maize at high plant densities and late planting dates. A randomized complete block design (RCBD) was used in a split-spilt plots arrangement with four replications and three factors. The first factor included planting dates (1st and 10th August), the second factor included plant densities (70 and 90 thousand plants ha-1), and the third factor included varieties (Baghdad 3, Al -Maha, TW-78, TW-345, IY-355 and IY-207). The results showed that the plants planted on the first date of 1stAugust excelled by giving the highest rate of number of ears plant (1.13 ear plant-1) and Individual plant yield (180.72 gm plant-1), while the traits of number of grains ear and weight of 100 grains were not significantly affected. The traits the number of grains ear-1 and Individual plant yield were significantly affected by increasing plant density, as the density exceeded 70,000 plant ha-1 with their highest mean reaching (613.3 grains ear-1 and 178.04 gm plant-1) respectively, while the traits of number of ears plant and the weight of 100 grains were not significantly affected. The varieties differed significantly in the mentioned traits, with the exception of the number of ears. The Iraqi variety Baghdad 3 had the highest mean of grains number per ear (642.0 grains ear-1), and the Egyptian variety TW-78 gave the highest mean weight of 100 grains and individual plant yield, which reached 31.64 gm and 178.05 gm plant-1 sequentially. The binary interaction (planting dates ×plant density) did not appear significant in the mentioned traits, while the results showed the response of the varieties to delaying the planting dates from 1st to 10th August for the mentioned traits with the exception of the number of grains per ear and the weight of 100 grains. The interaction of varieties and plant densities did not show significance for the mentioned traits, while the three-way interaction (planting dates × plant densities × varieties) showed significance for the weight of 100 grains and individual plant yield.